Analisis Penerimaan dan Pengeluaran Barang Umum Non Curah Pada Gudang Perbekalan PT. Semen Padang - Amanda Febria Sari (Jurnal Optimasi Sistem Industri)
Inventory has its advantages and disadvantages. The advantage of this inventory is to be able to anticipate the urgent needs of the company, meet the demand from users. But this stock has a loss, which can increase the costs to be incurred by the company so as to reduce the advantage held by the company. The more the amount of inventory in warehouse, the more the cost of inventory that must be removed and inventory turnover (ITO) which produced the lower. One way to do inventory control is to determine the optimal order quantity. The method used to determine the optimal number of reservations is to use the EOQ method by considering the amount of safety stock and reorder point when done. Based on the calculations have been performed for the optimal order quantity are 2,019 bottles of oxygen, welding wirerod is 14,795 stems, and 185 stem of pipe metal. By doing of EOQ to inventory control obtained by the method of ITO increases the weld wire and pipe metal from 0.0392 to 1.1010 at the welding wire and from 0.2949 to 0.8627 on a pipe metal. However, the oxygen has decreased from 1.9238 to 1.6094 so that it can be concluded that the EOQ method can not be applied to the oxygen, but can be applied to the welding wire and pipe metal.